PENYULUHAN HUKUM DAN PENCEGAHAN CYBERBULLYING DI MEDIA SOSIAL PADA SISWA SMA NEGERI 1 INDRALAYA - Cynthia Azhara; Meria Utama; Ahmad Idris; Rizka Nurliyantika; Ricky Saputra; Raesitha Zildjianda; Santriana; Biyes Nurul (CV. Cendikiawan Muda Sriwijaya, 2024)
The target population of this study is the students of Indralaya Public Highschool Number 1. According to UNICEF data from 2022, 45% of 2,777 children in Indonesia have admitted to being victims of cyberbullying. Therefore, it is necessary to provide legal counseling and prevention of cyberbullying to teenagers, especially high school students. A survey conducted by the Ministry of Women and Child Protection in collaboration with Child Fund International in 2023 revealed that 49.1% of adolescents in DKI Jakarta, Central Java, Lampung, and East Nusa Tenggara (NTT) admitted to being bullies, while 51% acknowledged experiences as victims of bullying. The service method entails the provision of counseling on the prevention of cyberbullying on social media among students in alignment with Law No. 1 of 2024 concerning the Second Amendment to Law No. 11 of 2008 concerning Electronic Information and Transactions.Moreover, the question and answer method was employed to ascertain the extent of students' comprehension of the material presented. The ensuing conclusion, substantiated by the students' inquiries and responses, indicates a persisting lack of comprehension regarding the impact and prevention of cyberbullying, particularly in the context of social media misuse. Keywords: legal; counseling; prevention; cyberbullying; Indralaya